THE ROLE OF SOFT SKILLS TRAINING IN EMPLOYEE PERFORMANCE - Kethankar B R (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Soft skills training play a crucial role in enhancing employee performance by improving communication, teamwork, leadership, adaptability, and problem-solving abilities. Unlike technical skills, which focus on job-specific expertise, soft skills determine how effectively employees interact with colleagues, clients, and management. In today’s competitive and dynamic work environment, organizations recognize the need to invest in soft skills training to boost productivity, foster a positive workplace culture, and improve customer satisfaction. This paper explores the significance of soft skills training in shaping employee performance and overall organizational success. Effective communication skills help employees convey ideas clearly and collaborate efficiently, reducing misunderstandings and conflicts in the workplace. Leadership and decision-making training empower employees to take initiative and handle responsibilities with confidence, fostering a proactive workforce. Additionally, adaptability training enables employees to embrace change and respond effectively to evolving market trends, ensuring business sustainability. Customer service training enhances client interactions, leading to better customer retention and brand loyalty. Moreover, emotional intelligence training equips employees with self-awareness and empathy, contributing to a healthier and more inclusive work environment. Case studies of leading Indian companies such as Tata Consultancy Services (TCS) and Infosys highlight the tangible benefits of soft skills training, including improved client satisfaction, enhanced team dynamics, and higher employee engagement. The findings suggest that organizations prioritizing soft skills training experience increased employee retention, better workplace collaboration, and overall business growth. In conclusion, soft skills training is essential for modern workplaces, ensuring employees develop the necessary interpersonal and problem-solving skills to thrive. Companies that invest in continuous soft skills development create a well-rounded, efficient, and motivated workforce, ultimately leading to long-term organizational success.